History and evidence show school sports help students win. (May 2016) - Bowen, Daniel H.; Hitt, Collin
Student participation in school sports has surged over the past half century. The greatest contributor to this increase has been Title IX, which required schools to expand opportunities for girls. Despite the perceived benefits and high levels of support from students and parents, interscholastic athletics constantly come under attack. The fervor for school-sponsored sports can get out of hand, but anything can be overemphasized. In spite of the myths about school sports, student-athletes generally do better in school than other students, not worse. The academic eligibility requirements that schools place on athletes have decreased dropout rates among at-risk students. The larger body of evidence shows that school sports have genuinely benefitted students and their school communities.